Awareness of Symptoms and Early Management of Hypoglycemia among Patients with Diabetes Mellitus - Sharma, Suresh K; Kant, Ravi (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Background: Hypoglycemia mostly occurs in diabetic patients on medications. Lack of awareness on hypoglycemic symptoms among patients may delay its identification and treatment. The symptoms of hypoglycemic symptoms among patients may delay its identification and treatment. Neglecting the symptoms of hypoglycemia and delaying treatment could cause poorer outcomes or morbidity. The present study was aimed to assess the awareness of symptoms of hypoglycemia and knowledge in early management of hypoglycemia among patients with diabetes.Methods: A Cross sectional study was done among 500 diabetes mellitus patients attending the outpatient department of AIIMS, Rishikesh, Uttarakhand in 2017. Patient with diabetes for over five years and who were on insulin treatment were included in the study. After obtaining an informed consent, knowledge on the symptoms and early treatment of hypoglycemia were collected. The data were analyzed by frequency and percentage.Results: The study included 500 diabetic patients, of which 55.5% were females. The common symptoms of hypoglycemia known to the study subjects were dizziness (84.4%), weakness (74.1%), and drowsiness (68.1%). Overall, 322 (64.4%) diabetic patients had good knowledge on hypoglycemia (knowledge of at least three symptoms of hypoglycemia together with at least one precipitating factor and at least one remedial measure). Regarding management of hypoglycemia, 49% patients preferred taking glucose powder or sugar with water as an immediate measure. Higher age, illiteracy, low socioeconomic status was associated with poor knowledge whereas treatment with insulin along with oral hypoglycemic agents was associated with good knowledge on hypoglycemia.Conclusion: Although the knowledge on the symptoms, remedial measures, and prevention of hypoglycemic episodes was good among the type 2 diabetic patients in the study, there were gap in knowledge on important aspects like precipitating factors, target levels etc., which need to be addressed by health care workers through regular educational programs.Jour of Diab and Endo Assoc of Nepal 2017; 1(1): 12-17